Role of Tetracycline in Corneal Neovascularization - Sameen Afzal Junejo, Mustafa Kamal, Arshad Ali Lodhi, Murtaza, Munawar Ahmed , Noman Ahmed Ghulam Haider (Pakistan Journal of Ophthalmology, 2015)
Purpose: To find the efficacy of topical tetracycline in corneal neovascularization. Material and Methods: In this prospective observational clinical analysis, patients more than fifteen year’s age of either sex were enrolled. Anterior segment slit lamp examination was performed. Fluorescein 1% dye and rose bengal were used to stain cornea at the bed and margins simultaneously. The area of corneal vascularization was measured in mm using 0.5% fluorescein dye. The percentage of neovascularized corneal areas to the entire cornea was calculated. Result: Out of twenty eight patients twenty one completed follow up period of four months. Among 21 patients males were 10 (47.6%), and females 11 (52.38%) with unilateral and bilateral corneal neo-vascularization. 15 (71.42%) responded well and showed reduction in corneal new vessels from 7 mm pretreatment to 2 mm (overall) post treatment at the end of fourth month. six patient showed poor or no response due to extended fibrosis. Conclusion: Topical tetracycline has remained quite instrumental in reducing superficial epithelial and sub-epithelial corneal new vessels. Key Words: Cornea; Neovascularization; Tetracycline; Therapeutic effect